Risk management approach using ash-based amendment blends for remediation of lead-contaminated urban soils and protection of public health - Loryssa M. Lake; Sarah B. Scott; Darryl B. Hood; Meagan Kellis; Mary M. Gardiner; Nicholas T. Basta (Elsevier, 2024)
Anthropogenic activities have left a legacy of contaminated vacant land, which disproportionately affects lower income communities and can have detrimental impacts on human health, particularly children. A management solution is needed to address this widespread lead contamination in urban soils of vacant lots. In this study, high-Fe biosolids incinerator ash (BIA) was evaluated for its ability to sequester soil Pb. Five blends were created using BIA and different amount of other products (dredge, biosolids compost, and yard waste compost) to determine the most effective treatment to reduce Pb bioaccessibility in the soil. The sorption capacity of the BIA for Pb was evaluated by mixing the BIA with Pb(NO3)2 at 1000 to 100,000 ​mg ​Pb/kg BIA. The contaminated soil from Cleveland, OH was treated with five BIA-based blends at a 1:1 (w/w) ratio, and Pb bioaccessibility was evaluated using USEPA Method 1340 ​at pH 2.5 and the Physiologically Based Extraction Test (PBET) at pH 2.5. BIA was a strong sorbent for Pb, sorbing ∼100% of the Pb from solution at 10,000 ​mg/L with only 41% bioaccessibility based on Method 1340 ​at pH 2.5. The blend containing 4.5%, 10%, or 19% BIA reduced the Pb bioaccessibility by 48% from the control based on both bioaccessibility methods. The bioaccessible Pb determined by PBET was less than that by USEPA Method 1340 ​at pH 2.5. However, similar reductions in bioaccessible Pb between blend-treated soils and the unamended soil were observed for all bioaccessibility methods. Plant growth assays showed the blends to have little to no significant impact on clover growth, mortality, or flower production, with the blend containing 10% BIA showing greater biomass yield. Results showed BIA-based blends were able to reduce bioaccessible Pb in the soil. This remediation approach may improve the urban living environment and protects public health.